SPARC Aggravates Blood-Brain Barrier Disruption via Integrin αVβ3/MAPKs/MMP-9 Signaling Pathway after Subarachnoid Hemorrhage - Takeshi Okada (Hindawi Limited, 2021)
Blood-brain barrier (BBB) disruption is a common and critical pathology following subarachnoid hemorrhage (SAH). We investigated the BBB disruption property of secreted protein acidic and rich in cysteine (SPARC) after SAH. A total of 197 rats underwent endovascular perforation to induce SAH or sham operation. Small interfering ribonucleic acid (siRNA) for SPARC or scrambled siRNA was administered intracerebroventricularly to rats 48 h before SAH. Anti-SPARC monoclonal antibody (mAb) 236 for functional blocking or normal mouse immunoglobulin G (IgG) was administered intracerebroventricularly 1 h after SAH. Selective integrin αVβ3 inhibitor cyclo(-RGDfK) or phosphate-buffered saline was administered intranasally 1 h before SAH, along with recombinant SPARC treatment. Neurobehavior, SAH severity, brain edema, immunohistochemical staining, and Western blot were evaluated. The expression of SPARC and integrin αVβ3 was upregulated after SAH in the endothelial cells. SPARC siRNA and anti-SPARC mAb 236 prevented neuroimpairments and brain edema through protection of BBB as measured by IgG extravasation 24 and 72 h after SAH. Recombinant SPARC aggravated neuroimpairments and cyclo(-RGDfK) suppressed the harmful neurological effects via inhibition of activated c-Jun N-terminal kinase, p38, and matrix metalloproteinase-9 followed by retention of endothelial junction proteins. SPARC may induce post-SAH BBB disruption via integrin αVβ3 signaling pathway.